2021
DOI: 10.1021/jacs.1c04631
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemical Protonation of Metal Oxide Particles

Abstract: Metal oxides with surface protonation exhibit versatile physical and chemical properties suitable for use in many fields. Here, we develop an electrochemical route to directly protonize the physically assembled oxide particles, such as TiO 2 , Nb 2 O 5 , and WO 3 , in a Na 2 SO 4 neutral electrolyte, which is a result of electrochemically induced oxygen vacancies reacting with water molecules. With no need of electric connection among particles or between particles and conductive substrate, the electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…In contrast, H‐dopants are readily to react with hydroxyl ions in alkaline solution, result in collapse the oxide lattice and quick degradation of entire material. Moreover, hydrogenated metal oxides, though acquire unusual quasi‐metallic electronic structures during hydrogenation, maintain the merits of good biocompatibility and low cytotoxicity of the parent metal oxides, [ 20 ] as demonstrated by our first‐principle simulations and experiments. The quasi‐metallic electronic structures bestow them metal‐like abilities of efficient NIR‐II light absorption, photothermal conversion, and heat conducting, together with other merits listed above, making them ideal PTA candidates.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, H‐dopants are readily to react with hydroxyl ions in alkaline solution, result in collapse the oxide lattice and quick degradation of entire material. Moreover, hydrogenated metal oxides, though acquire unusual quasi‐metallic electronic structures during hydrogenation, maintain the merits of good biocompatibility and low cytotoxicity of the parent metal oxides, [ 20 ] as demonstrated by our first‐principle simulations and experiments. The quasi‐metallic electronic structures bestow them metal‐like abilities of efficient NIR‐II light absorption, photothermal conversion, and heat conducting, together with other merits listed above, making them ideal PTA candidates.…”
Section: Introductionmentioning
confidence: 96%
“…25 When the GBLM is contacted with WO 3 , a galvanic cell will be established to drive the hydrogen insertion. 21,22 Successful demonstrations based on WO 3 semiconductor particles have been reported, 26 but how the treatment will affect the PEC process has not yet been explored. As an acid-stable metal oxide semiconductor with visiblelight response, WO 3 has many important applications in solardriven water splitting, electrochromism, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen intercalation can be a good choice for ion insertion, as reported by some successful examples based on WO 3 . , Theoretical simulations have indicated the feasibility of hydrogen doping into metal oxide semiconductors for improved PEC processes . However, the reported methods were either energy intensive (e.g., with an external bias) or time-consuming to dope the H into WO 3 . , To overcome these shortcomings, we focused on the utilization of the special features of liquid metals . For instance, gallium-based liquid metals (GBLMs), alloyed by gallium and other metals with a low work function, are liquid-phase reducing agents .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenation could be a potential approach to repair structural defects in metal oxides. 17 Zou et al found that the oxygen vacancies of VO 2 could be repaired quickly as it was treated by hydrogen doping. 18 Because we have developed a cost-effective acid−metal treatment for hydrogen doping of metal oxides at ambient conditions, 19 an alternative strategy of removing oxygen defects in metal oxides based on manipulation of hydrogen dopants is foreseeable.…”
mentioning
confidence: 99%
“…Hydrogenation could be a potential approach to repair structural defects in metal oxides . Zou et al found that the oxygen vacancies of VO 2 could be repaired quickly as it was treated by hydrogen doping .…”
mentioning
confidence: 99%